ARGONAUTE2 Mediates RNA-Silencing Antiviral Defenses against Potato virus X in Arabidopsis(1)([W])([OA]) - Jaubert, Marianne (American Society of Plant Biologists, 2011)
RNA-silencing mechanisms control many aspects of gene regulation including the detection and degradation of viral RNA through the action of, among others, Dicer-like and Argonaute (AGO) proteins. However, the extent to which RNA silencing restricts virus host range has been difficult to separate from other factors that can affect virus-plant compatibility. Here we show that Potato virus X (PVX) can infect Arabidopsis (Arabidopsis thaliana), which is normally a nonhost for PVX, if coinfected with a second virus, Pepper ringspot virus. Here we show that the pepper ringspot virus 12K protein functions as a suppressor of silencing that appears to enable PVX to infect Arabidopsis. We also show that PVX is able to infect Arabidopsis Dicer-like mutants, indicating that RNA silencing is responsible for Arabidopsis nonhost resistance to PVX. Furthermore, we find that restriction of PVX on Arabidopsis also depends on AGO2, suggesting that this AGO protein has evolved to specialize in antiviral defenses.